Autoimmune thyroid disease disrupts immune homeostasis in the endometrium of unexplained infertility women—a single-cell RNA transcriptome study during the implantation window - Xie, Jilai; Gu, Aiyuan; He, Huangyi; Zhao, Qiaohang; Yu, Ya; Chen, Jian; Cheng, Zhangliang; Zhou, Ping; Zhou, Qi; Jin, Min (Frontiers in Endocrinology, 2023)
Objective Autoimmune thyroid disease (AITD) is known to be associated with unexplained infertility in women. Although the presence of antithyroid antibodies have been speculated to be a marker of an immune imbalance that might lead to implantation failure, its underlying mechanism influencing the endometrial receptivity remains to be elucidated. In this study, we used single-cell RNA sequencing (scRNA-seq) to dissect immune microenvironment in endometrium of AITD patients during window of implantation (WOI). Methods We collected CD45+ immune cell populations of endometrium samples of unexplained infertile women with AITD (n=3), as well as samples of AITD- controls (n=3). The cells were then processed with 10X Genomics Chromium for further analysis. Results We characterized 28 distinct immune cell subtypes totally, and uncovered differences in the composition and gene expression patterns between AITD patients and controls. The proportions of T CD4+, cNK, ILC3, T CD8+GZMK+, T CD8+ Cytotoxic and ILC3 CD3E- cells were increased, and CD366+ uNK1 was decreased in AITD+ patients. And the abnormal expression of GNLY and chemokines was observed in AITD patients. In addition, uNK and T CD8+ Cytotoxic cells showed lower cytotoxicity but activation of immune response. Genes enriched in cell adhesion of ILC3 and Tregs were downregulated, while the number of ILC3 and Tregs were increased. Conclusion Immune imbalance exists in endometrium during WOI, which may impact embryo implantation.